2019
DOI: 10.3329/bjms.v18i2.40701
|View full text |Cite
|
Sign up to set email alerts
|

Factors Affecting Nurses’ Perceived Organizational Commitment: A Qualitative Study

Abstract: Objective: Nurses' organizational commitment is one of the most important factors that facilitates their professional evolution and influences the method of care provision, quality of care, and patients' satisfaction. The aim of this study was identified the factors that affect nurses' perceived organizational commitment. Material and Methods: This qualitative study, conducted on 16 clinical nurses employed in Social Security Hospital of Khorramabad, Iran, during five months from May to September 2015, used de… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
3
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 6 publications
(5 citation statements)
references
References 26 publications
(38 reference statements)
1
3
0
Order By: Relevance
“…The results of a qualitative study carried out by the present researcher, concerning organizational commitment indicated that dissatisfaction with annual performance appraisal was one of the causes of nurses' indifference towards their work environment (Sepahvand, Atashzadeh-Shoorideh, Parvizy, & Zagheri-Tafreshi, 2018). This finding is consistent with studies that demonstrated that performance appraisal had a significant positive impact on nurses' intrinsic motivation.…”
Section: Literature Reviewsupporting
confidence: 89%
“…The results of a qualitative study carried out by the present researcher, concerning organizational commitment indicated that dissatisfaction with annual performance appraisal was one of the causes of nurses' indifference towards their work environment (Sepahvand, Atashzadeh-Shoorideh, Parvizy, & Zagheri-Tafreshi, 2018). This finding is consistent with studies that demonstrated that performance appraisal had a significant positive impact on nurses' intrinsic motivation.…”
Section: Literature Reviewsupporting
confidence: 89%
“…Due to this, the impact of fatigue may be an important factor in rationing nursing care, especially in the group of nurses working with children with hematological disease. Moreover, numerous evidence and studies have indicated that overwork, fatigue and intense stress in the nursing profession can lead to a reduction in organizational commitment [ 8 ], which also affects care rationing [ 3 ].…”
Section: Introductionmentioning
confidence: 99%
“…This indicate that nurses who perceived their work environment and living conditions are supportive intended to work and stay more in remote and rural areas than other nurses. Related findings from other literatures suggest that supportive work environment and living conditions can increase rural retention at work among nurses [36][37][38][39] .…”
Section: Discussionmentioning
confidence: 84%